2021
DOI: 10.1039/d0tc04266h
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional properties existing in Ln–nitronyl nitroxide single-chain magnets

Abstract: Taking advantage of a nitronyl nitroxide radical ligand 8-QNNIT (1) (8-quinolyl-4,4,5,5-tetramethyl-imidazoline-1-oxyl-3-oxide) and the Ln(hfac)32H2O (LnIII = Tb 2 and Dy 3; hfac = hexafiuoroacetylacetonate), two Ln-radical one-dimensional chains [Ln(hfac)3(8-QNNIT)]n were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Molecular magnetic materials especially single-molecule magnets (SMMs) exhibit slow magnetic relaxation behavior at low temperatures. With the continuous improvement of spin-reversal barrier and blocking temperature, SMMs have been expected to show increasing competitiveness in the fields of high-density information storage, quantum processing, and spintronics . It is an effective way to modulate the SMMs’ performance by the combination of lanthanide (Ln) centers and radical ligands. The paramagnetic radicals can penetrate into the deeply buried 4f orbitals of Ln ions, which may facilitate the direct exchange coupling between Ln ions and radical spins. However, this strategy usually requires burdensome synthetic methods (such as redox reactions triggered by chemical reagents) and is carried out under anhydrous and/or anaerobic conditions. Seeking a convenient way to control the magnetic behavior is crucial for the design of molecular devices.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular magnetic materials especially single-molecule magnets (SMMs) exhibit slow magnetic relaxation behavior at low temperatures. With the continuous improvement of spin-reversal barrier and blocking temperature, SMMs have been expected to show increasing competitiveness in the fields of high-density information storage, quantum processing, and spintronics . It is an effective way to modulate the SMMs’ performance by the combination of lanthanide (Ln) centers and radical ligands. The paramagnetic radicals can penetrate into the deeply buried 4f orbitals of Ln ions, which may facilitate the direct exchange coupling between Ln ions and radical spins. However, this strategy usually requires burdensome synthetic methods (such as redox reactions triggered by chemical reagents) and is carried out under anhydrous and/or anaerobic conditions. Seeking a convenient way to control the magnetic behavior is crucial for the design of molecular devices.…”
Section: Introductionmentioning
confidence: 99%
“…Nitronyl nitroxides are thermodynamically stable due to their electron-delocalized structure. Therefore, it is widely used as a spin carrier in the design of molecular magnetic materials, ,, with the expected AF or ferromagnetic (FM) spin-exchange interaction. , In previous works, the primary strategy was to obtain higher spin organic magnetic materials based on molecular topology, , like π-conjugated rigid molecules, metal ion coordination molecules, , and self-assembled molecules. …”
Section: Introductionmentioning
confidence: 99%
“…9 In 2021, Li et al reported 1D chains [Ln(hfac) 3 (8-QNNIT)] n (Ln = Tb, Dy), which displayed SCM behaviors and optical or/and thermodynamics properties that coexist in the molecular unit. 10 Recently, investigations into SCMs have also focused on Cu–Ln-radical heterotrispin chains. 11…”
Section: Introductionmentioning
confidence: 99%
“…9 In 2021, Li et al reported 1D chains [Ln(hfac) 3 (8-QNNIT)] n (Ln = Tb, Dy), which displayed SCM behaviors and optical or/and thermodynamics properties that coexist in the molecular unit. 10 Recently, investigations into SCMs have also focused on Cu-Ln-radical heterotrispin chains. 11 On the other hand, Ln-based complexes may be excellent candidates as fluorescent sensors for detecting toxic gases, small molecules, cations and anions due to the narrow and typical fluorescent emissions of some Ln(III) ions.…”
Section: Introductionmentioning
confidence: 99%